Testing Various Pre-treatments on Artificially Waterlogged and Pitch-Contaminated Wood for Strontium Isotope Analyses - Snoeck, Christophe; Schulting, Rick J.; Brock, Fiona; Rodler, Alexandra S.; Van Ham-Meert, Alicia; Mattielli, Nadine; Ostapkowicz, Joanna (Frontiers in Ecology and Evolution, 2021)
Strontium isotope ratios (87Sr/86Sr) are commonly used in archaeological and forensic studies to assess if humans and fauna are local to the place they were found or not. This approach is largely unexplored for wooden artefacts recovered in archaeological contexts, as wood – in the rare instances it does survive – is often poorly preserved. One of the most common ways wood is preserved is through the anoxic conditions found in waterlogged contexts. A more unusual form of preservation is through submergence in natural pitch. These depositional media contribute their own strontium values to the in vivo 87Sr/86Sr wood values, which needs to be removed prior to analysis. Here we test several pre-treatment methods to remove potential strontium contamination from wood samples that were artificially immersed in seawater and pitch from Trinidad’s Pitch Lake. Water rinses and acid-leaching tests were carried out with hydrochloric acid and acetic acid to remove exogenous strontium from experimentally waterlogged wood. These tests removed large amounts of strontium from the samples and did not enable the recovery of the endogenous 87Sr/86Sr signal. For samples artificially immersed in pitch, the pre-treatments tested were based on radiocarbon dating procedures and carried out with and without the aqueous-based acid-base-acid (ABA) step. The use of organic solvents alone (methanol and toluene) removed exogenous strontium originating from the pitch. However, the ABA step eliminates large amounts of in vivo strontium from the samples. These tests show that 87Sr/86Sr values of wood are altered by the presence of pitch and water. With adequate pre-treatment using exclusively organic solvents, it may be possible to remove this contamination for samples immersed in pitch. However, the aqueous-based ABA pre-treatment should be avoided. The removal of contamination from waterlogged samples was unsuccessful with the current pre-treatment protocols and more research is needed. More importantly, and unexpectedly, 87Sr/86Sr values may extend outside of the mixing line between the wood’s endogenous strontium and the water. These results indicate the need for extreme caution when attempting to determine the provenance of waterlogged wood.